Vibrational Spectroscopy Characterization and Anticoagulant Activity of a Sulfated Polysaccharide from Sea Cucumber Athyonidium Chilensis - Matsuhiro-Yamamoto, B; Matsuhiro-Yamamoto, B; Torres-De la Fuente, R (2012)
Sin Editorial Disponible